2022
DOI: 10.1002/hed.27065
|View full text |Cite
|
Sign up to set email alerts
|

Association between body composition and survival in head and neck cancer patients undergoing radiotherapy

Abstract: BackgroundBody composition may influence the prognosis of head and neck cancer (HNC) patients. To find out the most crucial factors in this relationship, we explored the association between body composition and survival.MethodsIn this prospective longitudinal study, HNC patients who underwent radiotherapy (RT) from March 2017 to December 2018 were recruited. The association between body composition and survival was analyzed using Cox proportional hazard regression.ResultsFinal analysis included 316 patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Zhuang et al. discovered that skeletal muscle mass was an independent prognostic factor for OS in head and neck cancer patients 23 . Similarly, Sanchez et al.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Zhuang et al. discovered that skeletal muscle mass was an independent prognostic factor for OS in head and neck cancer patients 23 . Similarly, Sanchez et al.…”
Section: Discussionmentioning
confidence: 93%
“…9 Zhuang et al discovered that skeletal muscle mass was an independent prognostic factor for OS in head and neck cancer patients. 23 Similarly, Sanchez et al showed that body composition can be used as a novel prognostic factor with the potential to enhance bladder cancer patients' survival. 24 The findings of this research align with prior studies, indicating that SMD can serve as a standalone prognostic indicator for patients with MIBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation